Analysis of prepositions in elementary school’ textbooks: reflections based on linguistic analysis - Nunes, Jhulia Gino; Ataíde, Bruna Vitória Rocha; Moreira, Tatiana Aparecida (The ESPecialist, 2025)
This article analyzes the way in which prepositions are worked in the textbook “Português: Conexão e Uso, seventh degree (Elementary School)”, by Delmanto and Carvalho (2018), through a linguistic analysis. Therefore, we will use Mendonça (2006), Bezerra and Reinaldo (2020) and what the authors explain about Linguistic Analysis (LA), considered that, according to the studies by Franchi (1987) summarized by Bezerra and Reinaldo (2020), linguistic activity contributes to a efficient communication in different contexts, elucidating teaching based on levels of reflection among linguistic, epilinguistic and metalinguistic activities. Through this theoretical perspective we have focusing on analyzing the highlighted textbook. As results, we show how the textbook presents prepositions to students, verifying if it simplifies, expands or limits the mentioned content.